Boosting Students’ Vocabulary Mastery: How Effective Is the Frayer Model? - Anugrah, Nur Hawalia; Ardiana; Sastrawati, Ika (English Language Teaching Methodology, 2025)
Vocabulary mastery remains a persistent challenge for Indonesian senior high school students, necessitating effective instructional strategies. This study investigates the effectiveness of the Frayer Model in improving students’ vocabulary mastery at SMAN 14 Gowa. Employing a pre-experimental quantitative design, the study involved 36 tenth-grade students selected through purposive sampling. Data were collected using a 20-item vocabulary test administered as pre-test and post-test, covering nouns, verbs, adjectives, and adverbs. Over six instructional meetings, the Frayer Model was implemented to facilitate concept definition, example analysis, and contextual application. Statistical analysis using SPSS 24 revealed a significant improvement in students’ vocabulary scores, with the mean increasing from 67.22 to 82.22. The t-test results confirmed the model’s effectiveness (t-count = −9.065 > t-table = 2.030). This study contributes empirical evidence supporting the Frayer Model as a practical and effective approach to vocabulary instruction in EFL classrooms.